A Longitudinal-Bending Hybrid Linear Ultrasonic Motor and Its Driving Characteristic - Huajie Qu; Chendong Liu; Lei Zhang; Jianjun Qu; Baoyu Song (Shock and Vibration)
As a new type of driver, linear ultrasonic motor (LUSM) is widely used in the high-tech field because of its low speed, high thrust, low noise, and no electromagnetic interference. However, as an actuator used in microdevices, most of the existing LUSMs are large in size and not compact in structure. In order to overcome these limitations, a new structure of linear ultrasonic motor’s stator is developed in this paper. The stator is similar to a tuning fork structure, which is divided into three parts: two driving feet, two driving legs, and the driving body. By using the first-order longitudinal vibration mode of the whole stator and the unique partial second-order bending vibration mode of the driving legs to achieve vibration mode degeneracy, a mode hybrid linear ultrasonic motor that is easy to miniaturize is proposed. Its working principle is analyzed. The dynamic analysis of the stator is carried out by using finite element software. The structure dimension of the stator and the driving frequency under the working mode are determined. At the same time, the feasibility of driving feet synthesizing elliptical motion is verified theoretically and experimentally. In addition, the LUSM test setup is built. The effects of driving frequency and Vpp on stator stall force and average velocity are studied. The results show that the maximum stall force can reach 99 mN, and the average velocity of the motor is 88.67 mm/s with Vpp = 320 V and driving frequency 80.2 kHz. The proposed LUSM is appropriate for use in occasions with quick return characteristics, like the controlling valve or nozzle of the printer. The research results provide guidance for the stator design of the linear ultrasonic motor.